Electrospun polyacrylonitrile fibrous membrane for dust removal - Zhu, Xingcheng; Kim, Kiwoong (Frontiers in Materials, 2022)
Particulate matter(PM) pollution has become a serious threat to human health. Accordingly, an air filtration media that can efficiently remove particulate matter should be developed immediately. Nanofibrous membrane filter prepared by electrospinning technology has nanoscale diameter, high specific surface area, and relatively high porosity, which are suitable for dust removal. This paper explored the effects of electrospinning parameters on the microscopic morphology, fiber diameter, and pore size of polyacrylonitrile(PAN) nanofibrous membranes, including polymer solution concentration, applied voltage, and tip-to-collector distance. Thereafter, filtration efficiencies of electrospun PAN fibrous membrane and Polytetrafluoroethylene (PTFE), Cellulose acetate(CA), Nylon commercial filter were compared by removing smoke PMs. Results showed that fiber diameter and pore size increase with increasing concentration but decrease with increasing distance. With an increase in applied voltage, fiber diameter and pore size first decreased and increased thereafter. Lastly, filtration experimental results showed that filtration efficiency of electrospun PAN nanofibrous membranes was higher than that of those commercial filter membranes for ultra fine dust (0.3–0.5 μm).